Evaluasi Penerapan Standar Operasional Prosedur Dan Strategi Peningkatan Kualitas Layanan Di Envy Restaurant Hotel Holiday Inn Resort Baruna Bali - Setiawan, I Komang Didik; Rahmawati, Putu Indah (Jurnal Manajemen Perhotelan dan Pariwisata, 2020)
This study aimed to determine the standard operating procedures at Envy Restaurant, the implementation at Envy Restaurant, and strategies to improve service quality at Envy Restaurant. The research used a qualitative descriptive method. Data were collected observation, interviews and documentation. The subjects in this study were supervisors and staff in Envy Restaurant. The results of this study indicates that : (1) Envy restaurant does already have standard operating procedures and has been monitored in every implementation by managers or supervisors, but in the case of its application, it is still found to be incompatible with the standards owned; (2) To improve the quality of service in Envy Restaurant, it is also necessary to evaluate, give morningÂ  briefing, provideÂ  feedback, conduct role play training. It is important that superiors taking a persuasive approach to the staffs to do the job based on the standard procedure.